O sistema de disposição final dos resíduos sólidos na cidade de Manaus/AM: avaliação por meio do índice de qualidade de aterros de resíduos (IQR) - Santos, Luiz Eduardo Chaves (Brasil, 2023)
The Sanitary Landfill carries out actions that impact the way the waste generated is handled and conducted through an environmentally appropriate final destination, whether arising from civil construction, general commerce, industries, human beings and domestic animals, effluents, among others. The methodology applied in this course conclusion work was created from three moments: through the bibliographic review, the study carried out in the field (carried out between October and December 2022) and the synthesis and dissemination of the information obtained. All specific objectives (presentation of the disposal steps and techniques, in addition to the treatment of waste and its derivatives), application of the IQR Waste Landfill Quality Index and the general objective were successfully achieved. The final evaluation of the ASM obtained an excellent average score, reaching 8.9, on a scale that goes from 0 to 10.0 points, which makes the conditions for the functioning of the ASM adequate. In the end, a presentation of the system was elaborated in the form of a report after the synthesis of all the information, where the social, scientific, economic and public health importance that Sanitary Landfills present when they are well operated and managed was informed. In addition, existing deficiencies were presented in relation to the treatment of by-products generated by waste: the non-use of energy from biogas and insufficient treatment of percolates. Environmental education projects and updating this research through the IQR were presented as proposals for future work when the ASM approaches its closure.